2008
DOI: 10.2165/00002512-200825080-00006
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Predict Potentially Inappropriate Primary Care Prescribing in Older People?

Abstract: PIP amongst older people in the UK, although declining, remains at a high level. The association of PIP with age, deprivation and care homes is largely explained by the higher overall prescribing rates in these groups. The overall rise in prescribing emphasizes that polypharmacy does not necessarily increase PIP and attempts to reduce PIP by focusing on polypharmacy have not been successful. Reductions in PIP have previously been achieved by introducing national guidelines (e.g. co-proxamol), but might also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
4
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 24 publications
9
77
4
3
Order By: Relevance
“…Previous research has shown that a large number of drugs is a strong predictor for use of potentially inappropriate drugs [4]. We found that 72% of individuals with the indicator used PIP [3].…”
mentioning
confidence: 52%
“…Previous research has shown that a large number of drugs is a strong predictor for use of potentially inappropriate drugs [4]. We found that 72% of individuals with the indicator used PIP [3].…”
mentioning
confidence: 52%
“…Some studies have indicated that GPs do not consider themselves sufficiently competent to terminate medications initiated by specialists (Carey et al, 2008;Conner & Norman, 1995). Only one-third of physicians informed their patients about this subject at each interview.…”
Section: Discussionmentioning
confidence: 99%
“…Polypharmacy is a common phenomenon in older adults, and whilst targeting polypharmacy represents an obvious approach to reducing PIP, the distinction between appropriate and inappropriate polypharmacy is not clearly defined [22]. One study demonstrated that despite rises in polypharmacy in the UK, largely suspected to be associated with better chronic disease management, no subsequent increase in PIP was seen, indicating that prescribing more medications does not always translate to a rise in PIP [15]. In this era of increased focus on chronic disease management and multi-morbidities, this is an on-going challenge for those responsible for prescribing in primary care.…”
Section: Pip In the Uk (Application Of 52 Indicators)mentioning
confidence: 99%
“…The availability of clinical data allowed more complete assessment of PIP. The use of a large national database gave a clear insight into the more common issues in PIP nationally rather than the local focus of some previous studies [15].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation